PENGARUH CITRA TOKO DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN ULANG MELALUI KEPUASAN KONSUMEN (STUDI PADA TOKO BLUEBERRY LAHAT) - Armalinda Armalinda (Universitas Tidar, 2019)
The type of research used is explanatory research. Data collected using the method of observation, questionnaires and direct interviews. Data analysis techniques used are descriptive and inferential analysis techniques (validity test, reliability test, correlation coefficient, simple and multiple regression analysis, coefficient of determination, significance test (t test and F test) and path analysis (path analysis) .. From the results calculation of multiple regression analysis can be seen that the four variables have a strong relationship, where the largest multiple correlation coefficient (R) is in the hypothesis test Store image, promotion, and customer satisfaction with the repeat purchase decision of 0.908 with the magnitude of the determination coefficient (R2) is 0.824. From the results of the t test, it can be seen that all the independent variables have an effect on the dependent variable with a confidence level of 95% (= 0.05), obtained by t count > t table, then H0 is rejected Ha is accepted.